2016
DOI: 10.1073/pnas.1605873113
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the 3′ splice site RNA by the U2AF heterodimer involves a dynamic population shift

Abstract: An essential early step in the assembly of human spliceosomes onto pre-mRNA involves the recognition of regulatory RNA cis elements in the 3′ splice site by the U2 auxiliary factor (U2AF). The large (U2AF65) and small (U2AF35) subunits of the U2AF heterodimer contact the polypyrimidine tract (Py-tract) and the AG-dinucleotide, respectively. The tandem RNA recognition motif domains (RRM1,2) of U2AF65 adopt closed/inactive and open/active conformations in the free form and when bound to bona fide Py-tract RNA li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
64
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 57 publications
9
64
0
2
Order By: Relevance
“…undergoes a conformational transition during its transit time through the confocal volume [32] . As shown recently, the free U2AF65 protein exhibits dynamics as observed from the deviation from the static FRET line, while U2AF65 bound to RNA is significantly more rigid (Figure S8) [22] . Comparing these two-dimensional histograms of U2AF65 labeled with different acceptor fluorophores, we observe a significantly higher population of the closed state when the protein is labeled with Atto532/Cy5 or with Atto532/Atto647N than with Atto532/Alexa647.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…undergoes a conformational transition during its transit time through the confocal volume [32] . As shown recently, the free U2AF65 protein exhibits dynamics as observed from the deviation from the static FRET line, while U2AF65 bound to RNA is significantly more rigid (Figure S8) [22] . Comparing these two-dimensional histograms of U2AF65 labeled with different acceptor fluorophores, we observe a significantly higher population of the closed state when the protein is labeled with Atto532/Cy5 or with Atto532/Atto647N than with Atto532/Alexa647.…”
Section: Resultssupporting
confidence: 56%
“…A high FRET state (FRET efficiency 80%) is observed for the free form of U2AF65 for all the different combinations of fluorophores (Figure 1B , left ). This FRET state corresponds to a population of molecules dynamically switching between a closed and an open conformation [22] . When bound to RNA, U2AF65 adopts an open conformation, which is visible with a FRET efficiency of ~45% for all combinations of fluorophores (Figure 1B, right ).…”
Section: Resultsmentioning
confidence: 99%
“…Major U2AF2 conformations in the absence of RNA include “closed” and “open” structures that have been characterized by NMR, small-angle X-ray scattering, and single molecule Förster resonance energy transfer 1316 . The “open” U2AF2 conformation is selectively stabilized by RNA binding and has been characterized at high resolution by X-ray crystallography 15 .…”
mentioning
confidence: 99%
“…von Voithenberg et al . 35 showed that RRM1 and RRM2 undergo dynamic exchange between a closed or open orientation at equilibrium ( Figure 2). In the closed state, RRM1 and RRM2 do not bind RNA, but when the conformation is open, a polypyrimidine tract can bind.…”
Section: Rna Recognition Motifsmentioning
confidence: 99%